Поняття шкали простору невизначеності та його застосування - Diduk, N. N. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2019)
A new notion of uncertainty space scale is introduced which makes it possible: 1) to find something in common among all the well-known kinds of averages (in particular to separate the subclass of averaging uncertainty spaces); 2) to construct even analogues (even versions) for all averaging spaces. In future the even versions apparatus may be applied to construct even subspaces of uncertainty spaces.